Talleres de motivación para mejorar el rendimiento académico en los estudiantes del décimo año de educación básica, paralelo “a” de la unidad educativa Marieta de Veintimilla, periodo 2017-2018. - Gaona Giron, Karina Jessica (2019)
The academic performance is the form like the student expresses the learnt through the process of education- learning. The present study titled: WORKSHOPS OF MOTIVATION TO IMPROVE THE ACADEMIC PERFORMANCE IN THE STUDENTS OF THE TENTH YEAR OF BASIC EDUCATION, PARALLEL “To” OF THE EDUCATIONAL UNIT MARIETA OF VEINTIMILLA, PERIOD 2017-2018.Had like aim improve the academic performance through workshops of motivation in this population, This thesis frame in a descriptive study of transversal court with design preexperimental; they employed the methods: scientist, analytical-synthetic, inductivodeductivo, descriptive. It applied the Questionnaire M.To.P.And.-II, in a sample of 30 students, of the results (pre-test) considering the most significant data were, that for 100% of the investigated present low motivation in the capacity of work and performance; and with the same percentage of 100% manifest low intrinsic motivation, likewise, 93,33% show low motivation in the factor vagancia (with negative weight); afterwards of the application of the workshops of motivation (post-test), for 73,33% of the population investigated surpassed the low level to the high level in the capacity of work and performance; likewise for 83,33% the investigated go up of level of intrinsic motivation and finally, 66,66% show a half level of motivation in the factor vagancia, attaining show the effectiveness of the workshops of motivation.